Investigando a legitimidade: Estudo de atitudes de público em relação aos papéis do Estado e do mercado - Andrews, Christina W. [UNESP] (FapUNIFESP (SciELO), 2006)
Using data collected in nine countries - Argentina, Brazil, Chile, Czech Republic, Poland, Russian Federation, Finland, Germany and the USA - through the World Values Survey, the article analyses the validity of four variables with a supposed potential to evaluate the legitimacy level of the private sector vis-à-vis the public sector. This analysis in undertaken in the context of the discussions on the future of market reforms that were implemented in several countries in the past 20 years. The investigation adopted a two level strategy: first, the aggregated frequencies for the nine countries were analyzed, followed by a bivariate analysis aimed at verifying the internal consistency of the variables. The article concludes that the four variables under consideration do not compose a valid dimension capable of assessing the legitimacy of the public sector versus the private sector.
Keywords: Legitimacy; Market reforms; Political culture; Public opinion